Utilizing Biopsychosocial and Strengths‐Based Approaches Within the Field of Child Health: What We Know and Where We Can Grow. Issue 147 (March 2015) - Black, Jessica M.; Hoeft, Fumiko
Abstract: We continue to increase our understanding of the experiences and settings that contribute to positive developmental outcomes in childhood, and those that confer greater risk. Although the mechanisms by which the risk and protective factors affect developmental outcomes need to be further elucidated through research, converging findings from the field of child health (spanning both physical and mental health) indicate that a biopsychosocial approach is useful. Here, we examine the evidence that early experiences confer both risk and protective processes on biopsychosocial development in childhood, and touch on some implications for the life course. Although this interdisciplinary field of research has already garnered substantial attention, here we aim to highlight the opportunity to use a strengths‐based approach with the biopsychosocial model, with particular focus on children who experience prolonged stress. We close with consideration for future directions with an emphasis on policy and practice in clinical and educational settings to improve well‐being in these early stages of the life course. © 2015 Wiley Periodicals, Inc.